DIGITAL ADOPTION BY THE BANJARMASIN CITY COMMUNICATION, INFORMATICS, AND STATISTICS SERVICE TO RESPOND TO PUBLIC COMPLAINTS - Farid Nofiard; siti Kholisoh (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2025)
The utilization of Information and Communication Technology (ICT) in fostering effective governance has emerged as a pivotal area of inquiry within the domain of Government Science. One significant indicator of the efficacy of good governance is the government's capacity to manage public complaints effectively. The utilization of information and communication technology (ICT) has been identified as a crucial strategy to ensure a swift, accurate, and effective government response. The City Government of Banjarmasin, through the Dinas Komunikasi, Informasi dan Statistik Kota Banjarmasin, hereinafter referred to as the Diskominfotik Kota Banjarmasin, has presented a digital channel as a means of conveying complaints from the Banjarmasin community. This study employs the TOE Framework theoretical framework to examine the efficacy of the Diskominfotik Kota Banjarmasin's digital adoption in addressing public complaints. This study employs a qualitative approach, which demonstrates that the results of Diskominfotik Kota Banjarmasin have effectively responded to public complaints by optimally adopting digital, this success can be illustrated by the adequate fulfillment of the technological dimension, organizational dimension, and environmental dimension.